Wage Rigidity and Disinflation in Emerging Countries - Messina, Julián; Sanz-de-Galdeano, Anna (American Economic Association, 2014)
This paper examines the consequences of rapid disinflation for downward wage rigidities in two emerging countries, Brazil and Uruguay. Although wage rigidities are altered by disinflation, in neither of the two countries does price stability eliminate frictions in wage-setting mechanisms. In a context of individual wage negotiations and weak unions, disinflation in Uruguay puts an end to its history of indexation, but strong resistance to nominal wage cuts emerges. In strongly unionized Brazil, wage indexation is highly persistent, but the introduction of inflation targeting by the Central Bank in 1999 moves the focal point of wage negotiations to expected inflation.